PENEGAKAN HUKUM PENETAPAN TERSANGKA YANG BERASAL DARI PUTUSAN PRA-PERADILAN (STUDI KASUS PUTUSAN NO. 24/PID.PRA/2018/PN.JKT.SEL) - Yoyok Adi Syahputra; Madiasa Ablisar; Mahmud Mulyadi; Muhammad Ekaputra (Universitas Sumatera Utara, 2019)
ABSTRACT In the Criminal Procedure Code, it is indeed regulated regarding control over the implementation of forced efforts by law enforcement officials, namely through pretrial institutions, specifically and limited to Article 77 of the Criminal Procedure Code. However, based on Republic of Indonesia's Constitutional Court Decision No. 21 / PUU-XII / 2014, dated 28 April 2015 that the validity of the Determination of Suspects, searches and seizures is part of the pre-trial authority. As the object of study and analysis in this study will discuss a case study of the Pre-Judicial Decision of the South Jakarta District Court No. 24 / Pid.Pra / 2018 / PN.JKT.SEL. The verdict was a pre-trial ruling filed by the Anti-Corruption Society (MAKI) related to the Century Bank corruption case which attracted the attention of many people both from anti-corruption activists and law academics even the wider community also gave great attention. Based on the foregoing, then as for legal issues in this study, namely: legal considerations regarding the order to carry out an investigation and assign a suspect in a criminal act of corruption against a person based on the Pre-Judicial Decision of the South Jakarta District Court 24 / Pid.Pra / 2018 / PN.Jkt.Sel., Associated with the authority of pre-trial institutions; the obligation of the investigator to order to carry out investigations and determine suspects based on pretrial decisions in corruption; and whether the pre-trial ruling that states that someone is involved in a criminal act of corruption can be used as preliminary evidence that a person can be made a suspect in a criminal act of corruption, or not. KeyWords : law enforcement; determination of the suspect; and pre-judicial decisions.